Information Extraction for Vietnamese Real-Estate Advertisements - Phạm, Vi Liên (University of Engineering and Technology, 2017)
In recent years, real-estate market in Vietnam is growing rapidly which creates a lot of information about real-estate, especially information on advertising for buying and selling activities of real-estate development.